PENGARUH PRAKTIK MANAJEMEN SUMBER DAYAMANUSIA – ELEKTRONIK (MSDM-EL) TERHADAP KINERJA KARYAWAN YANG DI MEDIASI OLEH PRODUKTIVITAS ORGANISASI PADA RUMAH SAKIT GIGI DAN MULUT YARSI CEMPAKA PUTIH DKI JAKARTA - Dimas Setiawan (CV. Denasya Smart Publisher, 2026)
This study aims to determine the effect of Electronic Human Resource Management (E-HRM) and organizational productivity on employee performance at the Yarsi Cempaka Putih Dental and Oral Hospital in DKI Jakarta. This study uses a quantitative approach with a survey method through questionnaires. The sample used in this study consisted of 106 people selected using probability sampling. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the help of SmartPLS version 4.0 software to test the validity, reliability, and relationships between variables. The results showed that (1) MSDM-EL had a positive and significant effect on employee performance (ꞵ = 0.288; t = 2.992; p < 0.05), (2) MSDM-EL had a positive and significant effect on organizational productivity (ꞵ = 0.481; t = 5.824; p < 0.05), (3) organizational productivity has a positive and significant effect on employee performance (ꞵ = 0.555; t = 6.044; p < 0.05), (4) MSDM-EL has a positive and significant effect on employee performance through organizational productivity (ꞵ = 0.267; t = 4.842; p < 0.05).